CRISPR Cas9-mediated ablation of pyruvate carboxylase gene in colon cancer cell line HT-29 inhibits growth and migration, induces apoptosis and increases sensitivity to 5-fluorouracil and glutaminase inhibitor - Ngamkham, Jarunya; Siritutsoontorn, Siraprapa; Saisomboon, Saowaluk; Vaeteewoottacharn, Kulthida; Jitrapakdee, Sarawut (Frontiers in Oncology, 2022)
Pyruvate carboxylase (PC) is an important anaplerotic enzyme that replenishes the tricarboxylic acid cycle (TCA) intermediates. It prevents the collapse of the TCA cycle upon its intermediates are removed during high anabolic demand. We have recently shown that overexpression of PC protein was associated with staging, metastasis and poor survival of colorectal cancer patients. Herein, we generated the PC knockout (PC KO) colon cancer cell lines, HT-29, by CRISPR-Cas9 technique, as a model to understand the role of this enzyme in colorectal cancer. The PC KO HT-29 cell lines had no detectable PC protein and did not show abnormal cellular or nuclear structures. However, PC KO HT-29 cells showed a 50-60% reduction in their growth rate and a 60-70% reduction in migration. The deficient growth phenotype of PC KO HT-29 cells was associated with apoptotic induction with no apparent cell cycle disruption following five days of growth. Down-regulation of key lipogenic enzymes, including acetyl-CoA carboxylase-1 and fatty acid synthase, was also associated with growth inhibition, suggesting that the de novo lipogenesis is impaired. Furthermore, PC KO HT-29 cells were 50% and 60% more sensitive to 5-fluorouracil and glutaminase inhibitor, CB-839, at their IC50 concentrations, respectively, following 48 h exposure. The increased cytotoxicity of CB-839 to PC KO HT-29 cells was associated with increased poly (ADP-ribose) polymerase cleavage. However, this was not observed with PC KO cells exposed to 5-fluorouracil, suggesting that PC KO HT-29 cells were prone to CB-839-induced apoptosis. Collectively, these findings indicate that ablation of PC expression in HT-29 cells disrupts the metabolic homeostasis of cells and inhibits proliferation and migration, accompanied by apoptotic induction. This study highlights the crucial role of PC in supporting the survival of HT-29 cells during exposure to chemotherapeutic drugs.